FRI0222 Association between blood lead levels and gout: the united states national health and nutrition examination survey 2007–2014. (12th June 2018) - Cheung, T.T.; Tsoi, M.F.; Cheung, B.M.Y.; Lau, W.C.S.
Abstract : Background: Lead is a heavy metal with no physiological role in humans. It is well known that cxcessive exposure to lead is associated with cardiovascular, gastrointestinal and neurological complications. However, recent studies have demonstrated that lead can increase the tubular reabsorption of urate, resulting in hyperuricaemia and the development of gout. Although blood lead levels are dropping in the US general population, the association between low blood lead levels ad gout remains inconclusive. Objectives: To evaluate the relationship between serum blood lead levels and the development of gout in the US general population. Methods: Adult participants with blood lead measurements and self reported gout in NHANES 2007–2014 were included in the analysis. Results were analysed using SPSS complex sample module version 22. Logistic regression with sample weight adjustment was used to study the association between blood lead levels and gout. Odds ratio (OR) and 95% confidence interval (95% CI) were estimated. Sub-group analysis was conducted in participants with blood lead level <5 µg/dL. Results: 18837 adult participants were included in the analysis. 18 270 participants had blood lead levels below 5 ug/dL (The current reference range for acceptable blood lead levels in healthy persons without excessive exposure to environment source of lead). The prevalence of gout increased with blood lead levels. In the total population, the odd ratio of gout was 4.96 in subjects with blood lead levels above 2.21 ug/dL. After adjusting for body mass index, hypertension, renal function and use of diuretics, the odd ratio of gout was 2.65 which remained significant. The subgroup analysis of subjects with blood lead levels below 5 ug/ml showed similar findings. The risk of gout is increased when blood lead levels are higher than 1.43 ug/dL. Conclusions: Low blood lead levels are associated with gout. The risk of gout is increased when the blood lead level is higher than 1.43 ug/dL. Therefore, measures should be taken to minimise the environmental exposure to lead. Disclosure of Interest: None declared